Exploring factors related to goal scoring opportunities in professional football - Schulze, E.; Julian, R.; Meyer, T. (Science and Medicine in Football, 2022)
Purpose: Outscoring opponents is the primary goal in football. To optimise goal scoring opportunities (GSOs), it is important to understand the preceding physical and tactical performance. This observational study explored whether running behaviour prior to GSOs related to the subsequent outcome (goal or no goal) or contextual factors.